Bell's palsy in an adolescent girl - not always a neurologist's territory: A case report and review of literature - Latha M Sneha; Raichel Priyanka; Shanthini Thanga Tamilselvan; Julius Xavier Scott (Wolters Kluwer Medknow Publications, 2017)
Infections, inflammatory, and autoimmune conditions are the well-recognized etiologies of acute facial nerve paralysis in children. Bell's palsy is idiopathic peripheral facial nerve palsy. Cranial neuropathies do occur in children due to the central nervous system involvement by malignancies but uncommon in pediatric acute lymphoblastic leukemias and even rarer in acute myeloid leukemias (AMLs). We report a case of a 13-year-old girl who presented with acute facial nerve palsy, was being treated as Bell's palsy elsewhere and was later diagnosed to have AML.